Factors afecting educational success and continuity among Young people of Moroccan descent in Catalonia (Spain) - Pàmies Rovira, Jordi; Bertran Tarrés, Marta (IJERI: International Journal of Educational Research and Innovation, 2018)
International reports and research emphasize the relation between the results of young immigrants in school and social integration and, in observing their school situation, indicate that in most countries they are worse than their native counterparts. This is particularly true for those groups that have a history of critical contact with host societies as in the case of young people of Moroccan origin in Catalonia. In this Autonomous Community, Morroccan students have low levels of accreditation at the end of compulsory schooling, have higher dropout rates, and their continuity in post-compulsory education is also lower than their native counterparts. This tendency, however, makes invisible the trajectories of school success and the growing social participation of a considerable part of these young people of Moroccan origin of both sexes in Catalan society. This article presents the results of a research project that, based on the reconstruction of the biographical and academic trajectories of these young people of Moroccan origin and the contribution of agents involved in their schooling, transitions to the labor market and social integration, has analyzed the central factors that allow the development of their success trajectories and the consolidation of long-term academic aspirations. We pay attention to the results obtained regarding the four trends that have emerged in the most relevant research in the construction of the success trajectories: the support received from the family, the social capital emanating from the peer group, the positive school experience and the impetus received from intra-ethnic associationism.